#TITLE_ALTERNATIVE# - SOPIAH (NIM 20506047), SITI
Electrochemistry topic contains difficult concepts, that is illustrated in several misconceptions such as the concepts of electrodes, electrolytes, voltaic cells, electrolysis, etc. Electrolysis is a non-spontaneous process, so that electric currents are required to make the reactions occurred. Quantitative relationship between electric current and the amount of substances involved in electrolysis reactions was formulated in Faraday laws. The amount of sediment resulted from electrolysis in the cathode is determined by several factors. In this research, factors influencing sulphate copper condensation in electrolysis process with copper anode and cathode were analyzed. Factors under study include electric current, the duration of electrolysis, electrolysis temperature, and electrolyte concentrations. From the research results, it can be concluded that the increase of electric current, the increase in electrolysis time, the increase of electrolysis temperature up certain temperature, and the increase of electrolyte concentration resulted to the increase of the amount of sediment in the cathode. Electric current, the duration of electrolysis, electrolysis temperature, and electrolyte concentration that were used at electrolysis process determined the quality of sediment. The use of small electric current (0,1-0,2A) resulted to high efficiency in the sediment production, and produced smooth surface compared to large current (>1A). The temperature of 61 degrees C represents optimum temperature for electrolysis because at this temperature, the sediment was produced smoothly and in large amount. The deliverable of this research is a printed version of the module of experiment that can be used in school laboratory and an electronic version that was placed in elearning environment called Moodle (Modular Object Oriented Dynamic Learning Environment). Moodle have facilities for teaching-learning such as course material, assignment and quiz. Learning electroyslis via e-learning environment using Moodle is expected to enrich classroom teaching-learning, so that the process becomes better and motivate student to learn more meaningful and self-supporting.